Predicting capacities of runways serving new large aircraft - Gopalakrishnan, Kasthurirangan (Transport, 2008)
This paper presents a simplified approach for predicting the allowable load repetitions of New Large Aircraft (NLA) loading for airfield runways based on Non‐Destructive Test (NDT) data. Full‐scale traffic test results from the Federal Aviation Administration's National Airport Pavement Test Facility (NAPTF) were used to develop the NDT‐based evaluation methodology. Four flexible test pavement sections with variable (unbound layer) thicknesses were trafficked using six‐wheel and four‐wheel NLA test gears until the test pavements were deemed failed. Non‐destructive tests using a Heavy Weight Deflectometer (HWD) were conducted prior to the initiation of traffic testing to measure the pavement surface deflections. In the past, pavement surface deflections have been successfully used as an indicator of airport pavement life. In this study, the HWD surface deflections and the derived Deflection Basin Parameters (DBPs) were related to functional performance of NAPTF flexible pavements through simple regression analysis. The results demonstrated the usefulness of NDT data for predicting the performance of airport flexible pavements serving the next generation of aircrafts.First published online: 27 Oct 2010